Synergy of the Ministry of Religious Affairs, Nahdlatul Ulama, and Muhammadiyah in Driving Religious Moderation to Achieve Indonesia's SDGs Targets - Sekar Ayu Aryani; Erham Budi Wiranto; Ahmad Asroni; Waston; Siti Fauziyah; Muhamad Yusup (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study examines the synergy between the Ministry of Religious Affairs, Nahdlatul Ulama (NU), and Muhammadiyah in promoting religious moderation to contribute to Indonesia’s achievement of the Sustainable Development Goals (SDGs). The primary objective is to explore how these three key actors collaborate in fostering moderation and how their efforts align with SDG targets, particularly those focused on peace, justice, and strong institutions (Goal 16). Theoretical Framework: Theoretical frameworks of religious moderation and functionalism guide the study, emphasizing the importance of balanced religious practices in a pluralistic society. Literature Review: The literature review highlights the roles of NU and Muhammadiyah in religious moderation, noting their unique contributions: NU’s inclusive Islam Nusantara approach and Muhammadiyah’s emphasis on Wasathiyah Islam. These frameworks underscore the importance of tolerance, justice, and harmony in national life, aligning with Indonesia’s commitment to promoting peace and reducing social fragmentation. However, studies also point to challenges, such as ideological differences between the two organizations and their relationship with the government, which complicate cross-sector collaboration. Methods: A qualitative research methodology was employed, utilizing interviews, observations, and document studies to gather data from key informants within the Ministry of Religious Affairs, NU, and Muhammadiyah. Thematic and constant comparative analysis were applied to identify key patterns and themes, including the interplay between religious moderation, government policy, and SDG implementation. Results: The research findings reveal that while progress has been made in promoting religious moderation, the lack of effective collaboration between the government and religious organizations remains a significant barrier. NU’s close ideological ties with the government contrast with Muhammadiyah’s critical yet supportive stance, leading to fragmented efforts. This fragmentation hampers the full realization of shared goals, including the achievement of SDGs in Indonesia. Implications: The study’s implications suggest that strengthening cross-sectoral collaboration and aligning organizational efforts are essential for achieving religious harmony and advancing SDG targets. Novelty: The novelty of this research lies in its focus on the intersection of religious moderation and SDGs, offering insights into how religious actors can contribute to sustainable development.